Were there any Racial Legislations against the Roma during the Horthy Era? - Heindl, Péter (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
Hungarian historians still question the fact that in the Horthy era there were racially discriminative legislations in force regarding all Roma. However, by analyzing contemporary legislation, it can be proven that in the period between the two world wars the Roma people suffered severe institutional discrimination in Hungary. The present study aims to buttress up this argument. The discrimination was based on a military emergency decree issued in the middle of the First World War. This decree was not repealed after the war, but the situation of the Roma was instead aggravated by the new decrees built on it. These decrees have been impacting the Roma even to this day, as they have been obstacles to social integration for many decades. The author of this paper and his colleagues intend to publish a collection of the approximately fifty decrees of the era they have collected that contained legislations aimed at the Roma in the near future.